(untitled) (Journal of research in medical and health sciences, 2026)
Dyskeratosis congenita is a rare hereditary syndrome characterized by structural and functional abnormalities of telomeres. Clinically, it mainly manifests as premature aging of multiple tissues and organs, hematopoietic failure, and high incidence of malignant tumors. Current studies mostly focus on mutation screening of telomerase-coding genes, while the exploration of mechanisms by which epigenetic modifications participate in the occurrence and progression of the disease remains insufficient. As a highly specific histone deacetylase, SIRT6 plays an irreplaceable role in chromatin conformation stability, DNA damage repair and telomere structure maintenance. However, its expression profile, regulatory pattern and functional value in the pathological process of dyskeratosis congenita have not been systematically elucidated. In this study, telomere dysfunctional cells were used as an in vitro model to detect the transcription and translation levels of SIRT6, and to analyze the intrinsic correlation between its expression and relative telomere length. SIRT6 expression was intervened by gene silencing and overexpression techniques to observe its effects on cell proliferation, apoptosis and the expression of telomere-related proteins, and to explore the molecular pathway of SIRT6 in regulating telomere length maintenance. The results showed that SIRT6 expression was significantly decreased in dyskeratosis congenita model cells and was positively correlated with the degree of telomere shortening. Inhibition of SIRT6 further aggravated telomere attrition and cellular dysfunction, while upregulation of SIRT6 partially restored telomere structural stability and ameliorated pathological cellular phenotypes. SIRT6 maintains telomere length homeostasis and delays cellular senescence mainly through deacetylation of histones in telomere regions, optimizing chromatin compaction and enhancing the binding efficiency of telomere protective proteins. This study enriches the pathogenic mechanism of dyskeratosis congenita from the perspective of epigenetic regulation, and identifies SIRT6 as a potential intervention target for this disease.